KRISTALISASI PELARUT SUHU RENDAH PADA PEMBUATAN FRAKSI KAYA VITAMIN E MENGANDUNG TOKOTRIENOL DARI DISTILAT ASAM LEMAK MINYAK SAWIT [Low Temperature Solvent Crystallizationin Tocotrienol Containing Vitamin E Rich Fraction Preparation from Palm Fatty Acid D - Kgs Ahmadi; Teti Estiasih (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2011)
Palm Fatty Acid Distillate (PFAD) is a by-product of physical refining of CPO (Crude Palm Oil) in deodorization process. PFAD is a potential source of natural vitamin E, that besides tocopherol, also contains tocotrienol. Both have functions as antioxidant and vitamin. This research studied a method for obtaining vitamin E rich fraction that contained tocotrienol by low temperature hexane solvent crystallization. The elucidation factors were ratio of solvent to unsaponifiable fraction of PFAD(5:1, 6:1, and 7:1) and crystallization temperature (-20, -10, and 0°C). The experiment was conducted in factorial completely randomized design. The research showed that PFAD contains high tocotrienol. Low temperature solvent crystallization of unsaponifiable fraction gave 33.88% increase ofvitamin E concentration compared to control. Temperature and ratio of solvent to unsaponifiable fraction affected enrichment of vitamin E in PFAD. Later, saponification increased vitamin E content in unsaponifiable fraction of PFAD. Enrichment of tocopherol was higher than that of tocotrienol, supposed as a result of improper separation process in crystallization stage. Modulation of Vitamin E concentration during saponification of PFAD increased antioxidant activity compared to unsaponifiable fraction. The best result was achieved at ratio of solvent to unsaponifiable fraction of 6:1 and crystallization temperature of -10°C.